PENGEMBANGAN SISTEM MANAJEMEN BENGKEL MENGGUKANAKAN LARAVEL DENGAN METODE RAPID APPLICATION DEVELOPMENT (RAD) - Lestari, Nadya Putri (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Abstract. In the rapidly evolving vehicle repair service industry, an effective management system is essential to enhance operational efficiency. This study aims to develop a web-based management system using Laravel and the Rapid Application Development (RAD) methodology. The system is designed to assist in transaction recording, service management, and automatic invoice generation. The RAD methodology enables flexible and iterative development tailored to user needs. Laravel was chosen for its capabilities in database management, security aspects, and scalability. The system's key features include an automated cashier, service management, and invoice creation and printing. Testing results indicate that this system improves transaction efficiency, provides more accurate financial reports, and minimizes recording errors. By implementing this system, vehicle repair businesses are expected to enhance competitiveness, accelerate service delivery, and offer a better customer experience. The adoption of information technology in workshop management serves as a strategic solution to meet the challenges of the digital era.